PERANCANGAN LOGO RIGAFARA FUTSAL CENTRE DI JALAN BY PASS KOTA PADANG - ROBBIYAURI FAREN, Drs. Syafwan, M.Si, Eliya Pebriyeni, S.Pd., M.Sn (Universitas Negeri Padang, 2015)
Rigafara Futsal Centre is one of the futsal field name in the city of Padang. Rigafara Futsal Centre located at Jalan By Pass / Kapuk, exactly in front of the crossroads of Taruko 1 Padang housing. Inaugurated on April 5, 2010 by Mr. Syafrial. The absence of a logo that can represent fully the vision and mission to form the image / images to the existence of Rigafara Futsal Centre is very influential in the competition, therefore, the owners wanted to create an attractive logo and can fully represent the vision and mission to form the image / images to the presence of Rigafara Futsal Centre, in addition to the logo Rigafara futsal Centre will be created and charged with having a meaning that represent elements that represent Rigafara futsal futsal Centre. In order that can attract more players to play in Rigafara futsal Centre, as well as to differentiate futsal Rigafara futsal Centre with other futsal field rental.The design of the logo as the main promotional media Rigafara Futsal Centre, then through the media support, the necessary data analysis through 5W + 1H.This method is needed to strengthen and refine the design. This design results in the form of a logo that is expected to be a media campaign memorable by futsal players, and can capture more customers and become the place for choose for visitors and futsal players in the city of Padang.Keywords : Logo, Games, Futsal Centre, Rigafara